Functional specialization within medial frontal cortex of the anterior cingulate for evaluating effort-related decisions. - Walton, M; Bannerman, D; Alterescu, K; Rushworth, M (2003)
The rat medial frontal cortex (MFC) has been implicated in allowing animals to work harder to receive larger rewards. However, it is unknown what role the individual MFC regions [anterior cingulate cortex (ACC) and prelimbic-infralimbic cortex (PL-IL)] play in such decision making. To investigate this, we trained rats on a T-maze cost-benefit task with two possible courses of action, shown previously to be affected by complete MFC lesions. One response involved climbing a 30 cm barrier to obtain a large quantity of reward (high cost-high reward), whereas the other had a lower energetic demand but also a smaller reward gain (low cost-low reward). Before surgery, all animals preferred to select the high cost-high reward option. However, after excitotoxic ACC lesions, there was a complete reversal of behavior, with the ACC group selecting the low cost-low reward response on nearly every trial. In contrast, both control animals and rats with PL-IL lesions continued to choose to climb the barrier for the larger reward. When the same rats were tested on a delayed match-to-sample paradigm however, it was the PL-IL group that was significantly impaired at learning the response rule, with the performance of ACC rats being comparable with controls. This double dissociation indicates that the ACC is the important region within the MFC when evaluating how much effort to expand for a specific reward.